SCIENTIFIC MAP OF GENDER AND SUSTAINABLE DEVELOPMENT: BIBLIOMETRIC ANALYSIS AND NETWORK VISUALIZATION - Ikrima, Silky Firdaus (Lentera : Journal of Gender and Children Studies, 2026)
Research on gender and sustainable development has expanded significantly over the past two decades as global attention toward gender inequality grows as a major barrier to achieving the SDGs. This study aims to map the global scientific landscape on gender, feminist development, and sustainable development through bibliometric analysis and network visualization. The method involved analyzing 142 open-access Scopus articles using the keywords “feminist AND development AND gender AND economic”, processed with VOSviewer and Biblioshiny to identify research trends, influential authors and institutions, thematic clusters, and research gaps. The results indicate a substantial increase in publications after 2015, dominance of developed countries such as the United Kingdom and the United States, and key themes including renewable energy, corporate sustainability, and women’s empowerment. The study also reveals structural barriers within health and education systems that continue to limit women’s roles in development. This research concludes that interdisciplinary integration and increased representation of developing countries are essential for strengthening evidence-based policies toward more inclusive and gender-responsive sustainable development.